Dramatic Utilization of Close-up in Horror Movies - Mowafaq Majeed (الاكاديمي, 2018)
A cinematic shot is the basis of the film, regardless of the size, angle, or motion of this shot. However, the size of the footage and the process of showing or hiding the scene or cinematic personality has a certain speciality   related to the nature of cinematic treatment and the type of the movie especially those characterized by the employment of the close-ups to induce   ambiguity or spread the mental image of the dramatic events and this relationship between the close-up and horror films is what prompted the researcher to identify the title of the search as follows: